The Use Of Instructional Media On Student Learning Outcomes In Class V SDN 6 Banawa Selatan - Rika Safitri (Universitas Tadulako, 2020)
This research aims to determine the utilization of media on students ' learning in the V class of SDN 6 Banawa Selatan. This research is a qualitative descriptive, this study was conducted at SDN 6 Banawa Selatan. The study subjects were taken in 21 students. Data is collected through observations, interviews, polls and documentation, data processing is a qualitative analysis of the descriptive. To assess the utilization of learning media in the V class of SDN 6 South Banawa can be measured by showing material mastery indicators, learning approaches, use of learning resources and learning media, student engagement, learning evaluation, reflection/making summaries, follow-up to students ' understanding. The indicator is then analyzed by quantitative calculations so that the results of answers from 21 students can be seen from the percentage of answers strongly agreed at 42%, while the 35% answered agree, 15% answered less concur and 7% answered disagree. So based on that data can be concluded that from the 4 alternative answers available, the students prefer very much agree and at least choose not agree. This means the utilization of learning media is in accordance with the expected media.